2017
DOI: 10.1523/jneurosci.0986-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Graded Elevation of c-Jun in Schwann CellsIn Vivo: Gene Dosage Determines Effects on Development, Remyelination, Tumorigenesis, and Hypomyelination

Abstract: Schwann cell c-Jun is implicated in adaptive and maladaptive functions in peripheral nerves. In injured nerves, this transcription factor promotes the repair Schwann cell phenotype and regeneration and promotes Schwann-cell-mediated neurotrophic support in models of peripheral neuropathies. However, c-Jun is associated with tumor formation in some systems, potentially suppresses myelin genes, and has been implicated in demyelinating neuropathies. To clarify these issues and to determine how c-Jun levels determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 45 publications
6
90
0
Order By: Relevance
“…In other words, Tet-On/c-Jun-modified SCs were not likely to suppress myelination in the later repair stage. Thus, our results and previous findings by Fazal et al (59) indicate that time-restricted expression of c-Jun in SCs is relatively safe and beneficial for nerve repair.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In other words, Tet-On/c-Jun-modified SCs were not likely to suppress myelination in the later repair stage. Thus, our results and previous findings by Fazal et al (59) indicate that time-restricted expression of c-Jun in SCs is relatively safe and beneficial for nerve repair.…”
Section: Discussionsupporting
confidence: 86%
“…The present study focused on the controlled expression of the c-Jun gene to provide time-restricted neurotrophic support for nerve regeneration, whereas previous studies have also showed that c-Jun is associated with tumor formation in some systems (56), potentially suppresses myelin genes (57), and has been implicated in demyelinating neuropathies (58). It was reported that more than 1000 genes were regulated by c-Jun in SCs after nerve injury, including the up-regulation of GDNF, sonic hedgehog, oligodendrocyte transcription factor 1, inhibitor of DNA binding 2, SRY-box 2, and runt-related transcription factor 2 and the down-regulation of myelin protein zero, myelin basic protein, and peripheral myelin protein 22 (48,59). Thus, up-regulation of c-Jun in SCs for nerve repair might raise the concern about the side effects of tumor formation and hypomyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to trigger dedifferentiation results at least in part from its ability to repress Egr2 and to directly antagonize myelin gene expression (Parkinson et al, ; Parkinson et al, ). Effects on proliferative properties and on activation of the repair program likely involve additional downstream mediators such as Runx2, the activator of the unfolded protein response Chop or specific microRNAs (Arthur‐Farraj et al, ; Hung, Sun, Keles, & Svaren, ), and are sensitive to the exact cJun levels (Fazal et al, ).…”
Section: Transcriptional Control Of Peripheral Remyelinationmentioning
confidence: 99%
“…As a result, regeneration of motor and sensory axons, and the survival of sensory neurons and facial motor neurons are severely compromised if Schwann cell c-Jun is inactivated. Conversely, in situations where normal regeneration is impaired, such as after chronic denervation and in aging animals, enhanced expression of Schwann cell c-Jun promotes axonal regeneration(Parkinson et al, 2008;Arthur-Farraj et al, 2012;Fontana et al, 2012;Fazal et al, 2017;Wagstaff et al, 2017;Figlia, Gerber, & Suter, 2018). Interestingly, macrophage recruitment and Schwann cell numbers, at least at early time points after injury, are less affected in the absence of c-Jun than other aspects of the injury response(Arthur-Farraj et al, 2012).…”
mentioning
confidence: 99%